2009
DOI: 10.1007/s11162-009-9151-x
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Student Success: Factors Influencing the Persistence and Transfer Decisions of Latino Community College Students Enrolled in Developmental Education

Abstract: This study examined the impact of a set of theoretically-derived predictor variables on the persistence and transfer of Hispanic community college students. Early models of student persistence have been validated primarily among 4-year college students. While the constructs have been well-established, the relationships of those relevant factors remain unexamined among community college transfer students, and specifically, among Hispanic students enrolled in developmental coursework and planning to transfer fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
186
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(201 citation statements)
references
References 41 publications
12
186
1
2
Order By: Relevance
“…Moreover, participation in multiple SL courses was associated with an even higher likelihood of degree attainment. Similar to previous research, individual student characteristics, such as cumulative GPA and units earned, gender, and social-economic status, were factors associated with student graduation within six years (Astin & oseguera, 2005;Crisp & Nora, 2010;DeAngelo et al, 2011;Pike et al, 2014). However, similar to Lockeman and Pelco (2013), controlling for these factors found that SL participation had a significantly positive association with graduation within six years for first-time freshman.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, participation in multiple SL courses was associated with an even higher likelihood of degree attainment. Similar to previous research, individual student characteristics, such as cumulative GPA and units earned, gender, and social-economic status, were factors associated with student graduation within six years (Astin & oseguera, 2005;Crisp & Nora, 2010;DeAngelo et al, 2011;Pike et al, 2014). However, similar to Lockeman and Pelco (2013), controlling for these factors found that SL participation had a significantly positive association with graduation within six years for first-time freshman.…”
Section: Discussionsupporting
confidence: 75%
“…Though a robust body of research has found that particular individual student characteristics, such as gender, race and ethnicity, economic status, and academic preparedness correlate with persistence and degree completion (Astin & oseguera, 2005;Crisp & Nora, 2010;DeAngelo, franke, Hurtado, Pryor, & Tran, 2011;Pike, Hansen, & Childress, 2014), these characteristics are not necessarily inevitable determinants of which students can succeed. Recent studies have shown that many institutions have demonstrated progress in increasing graduation rates for many students represented by these traits (Nguyen, Bibo, & Engle, 2012a;Nguyen, Bibo, & Engle, 2012b;Lynch & Engle, 2010a;Lynch & Engle, 2010b).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Numerous higher education scholars have recognized Rendón's contributions to the literature, even when her validation theory has not garnered the kind of attention of the likes of Vincent Tinto, for example, in explicating why 52 college students stop attending college or why they may experience difficulties (e.g., Barnett, 2010Barnett, , 2011Crisp & Nora, 2010;Dowd et al, 2011;Gildersleeve, 2011;Hurtado, Cuellar, & Guillermo-Wann, 2011;Nora, Urick, & Quijada Cerecer, 2011b;Rendón Linares & Muñoz, 2011;Tinto, 2012a).…”
Section: Mattering and The College Studentmentioning
confidence: 99%
“…Responding in part to the assumptions researchers and practitioners often make in applying theoretical or conceptual models to college students, Tinto noted recently that individuals often "make assumptions to simplify what would otherwise be very complex analyses" (Tinto, 2012b, p. 254), particularly in the case of constructs such as academic and social integration that have been operationalized in very different forms across studies (e.g., Barnett, 2006Barnett, , 2010Bean, 1982;Bean & Eaton, 2000;Berger & Braxton, 1998;Braxton, 1999;Braxton & Hirschy, 2005;Braxton & Lien, 2000;Braxton & McClendon, 2001;Butcher, 1997;Cabrera, Castaneda, Nora, & Hengstler, 1992a;Cabrera, Nora, & Castaneda, 1993;Crisp & Nora, 2010;Deil-Amen, 2011;Hagedorn, Maxwell, & Hampton, 2001;Hoffman, Richmond, Morrow, & Salomone, 2002;Hurtado & Carter, 1997;Karp, Hughes, & O'Gara, 2010;Kraemer, 1997;Nora et al, 2005;Nora & Crisp, 2012;Pascarella & Chapman, 1983;Pascarella & Terenzini, 1980;Rendón, 1994;Rendón et al, 2000). In sum, the operationalization of such constructs is often simplified for the ease of data collection and analysis.…”
mentioning
confidence: 99%
“…For instance, Latino male students placed in a developmental education curriculum often struggle with completing these courses (Acevedo-Gil, Santos, Alonso, & Solórzano, 2015;Crisp & Nora, 2010;Harris & Wood, 2013). Unfortunately, students who spend more time in developmental education courses are at a higher risk of becoming discouraged and dropping out since they are investing in non-college credit courses (Bettinger, Boatman, & Long, 2013;Crisp & Nora, 2010;Harris & Wood, 2013).…”
Section: Review Of the Literature Understanding Community College Degmentioning
confidence: 99%